An Improved Solution to Generation Scheduling Problem Using Slime Mold Algorithm - Zhu, Zixuan (Frontiers in Energy Research, 2022)
Slime Mould Algorithm (SMA) is a novel meat-heuristic search that replicates the characteristics of slime mould during oscillation. This is presented in a novel mathematical formulation that employs changeable weights to modify the sequence of both negative and positive propagation waves in order to build a mechanism for linking food availability with intensive exploration capacity and exploitation affinity. The paper demonstrates how to solve a non-convex and cost-effective load dispatch issue (ELD) in an electric power system using the SM method. The efficacy of SMA is explored for single area economic load dispatch on small scale power systems, using 3-, 5-, and 6-unit test systems, and the results are validated by comparing the results to those of other well-known meta-heuristic algorithms.